The importance of determining the severity of ichthyosis. - Turaeva, F.A.; Mannanov, A.M. (European Journal of Pediatric Dermatology, 2024)
Ichthyosis is a rare genetic skin disease that typically appears at birth or within the first few months of life. It is caused by mutations in some genes that interfere with the normal development of keratinocytes, causing thickening and peeling of the skin that resembles fish scales. The purpose of this study is to develop and evaluate a comprehensive, easy-to-use tool to measure the overall severity of body ichthyosis in adults and children. In this article an overview of several systems, among the most suitable and convenient, for assessing the severity of ichthyosis is provided. The use of a severity rating system in patient observation is also presented.